Racial/Ethnic Differences in 30-Day Mortality for Heart Failure and Pneumonia in the Veterans Health Administration Using Claims-based, Clinical, and Social Risk-adjustment Variables - Silva, Gabriella C; Jiang, Lan; Gutman, Roee; Wu, Wen-Chih; Mor, Vincent; Fine, Michael J; Kressin, Nancy R; Trivedi, Amal N (Medical care, 2021)
Prior studies have identified lower mortality in Black Veterans compared with White Veterans after hospitalization for common medical conditions, but these studies adjusted for comorbid conditions identified in administrative claims. The objectives of this study were to compare mortality for non-Hispanic White (hereafter, "White"), non-Hispanic Black (hereafter, "Black"), and Hispanic Veterans hospitalized for heart failure (HF) and pneumonia and determine whether observed mortality differences varied according to whether claims-based comorbid conditions and/or clinical variables were included in risk-adjustment models. This was an observational study. The study cohort included 143,520 admissions for HF and 127,782 admissions for pneumonia for Veterans hospitalized in 132 Veterans Health Administration (VA) Medical Centers between January 2009 and September 2015. The primary independent variable was racial/ethnic group (ie, Black, Hispanic, and non-Hispanic White), and the outcome was all-cause mortality 30 days following admission. To compare mortality by race/ethnicity, we used logistic regression models that included different combinations of claims-based, clinical, and sociodemographic variables. For each model, we estimated the average marginal effect (AME) for Black and Hispanic Veterans relative to White Veterans. Among the 143,520 (127,782) hospitalizations for HF (pneumonia), the average patient age was 71.6 (70.9) years and 98.4% (97.1%) were male. The unadjusted 30-day mortality rates for HF (pneumonia) were 7.2% (11.0%) for White, 4.1% (10.4%) for Black and 8.4% (16.9%) for Hispanic Veterans. Relative to White Veterans, when only claims-based variables were used for risk adjustment, the AME (95% confidence interval) for the HF [pneumonia] cohort was -2.17 (-2.45, -1.89) [0.08 (-0.41, 0.58)] for Black Veterans and 1.32 (0.49, 2.15) [4.51 (3.65, 5.38)] for Hispanic Veterans. When clinical variables were incorporated in addition to claims-based ones, the AME, relative to White Veterans, for the HF [pneumonia] cohort was -1.57 (-1.88, -1.27) [-0.83 (-1.31, -0.36)] for Black Veterans and 1.50 (0.71, 2.30) [3.30 (2.49, 4.11)] for Hispanic Veterans. Compared with White Veterans, Black Veterans had lower mortality, and Hispanic Veterans had higher mortality for HF and pneumonia. The inclusion of clinical variables into risk-adjustment models impacted the magnitude of racial/ethnic differences in mortality following hospitalization. Future studies examining racial/ethnic disparities should consider including clinical variables for risk adjustment.